Análise de livros didáticos à luz do modelo MTSK: um foco nos números racionais - Batista, Éverton Ferraz Marcelino (2023)
This dissertation brings an analysis of two 6th grade mathematics textbooks, which were validated in the last three years of the National Book and Didactic Material Program (2014, 2017 and 2020). The analysis consisted of raising, using a qualitative methodology of a documental nature, which specialized knowledge for the teaching of rational numbers were presented by the authors. As a parameter for the analyses, research was used whose results sought to identify the mobilization of the teacher's specialized knowledge for the teaching of rational numbers from the MKT model (Mathematical Knowledge for Teaching), by Ball, Thames and Phelps (2008) and the PCK, by Shulman (1987), and the results of these surveys formed a knowledge base for the analysis of textbooks. For the categorization of the specialized knowledge present in the works, the model of Specialized Knowledge of Mathematics Teachers (or of Teachers who Teach Mathematics), the MTSK (Mathematics Teachers' Specialized Knowledge) by Carrillo et al (2013), was used.The data presented in the analyzes indicate an emphasis on the part of the authors in the development of specialized knowledge in the “phenomenological” and “representational” aspects, with emphasis on Araribá Mais Mathematica in the latter scope. However, a relevant number of gaps was highlighted regarding aspects of “definitions and image of a concept” and “associated meanings” in both books. It was also possible to verify that both books demonstrate specialized knowledge for teaching in terms of “auxiliary connections” and “validation modes”, all of which are related to mathematical knowledge. With regard to didactic knowledge of the content, the data in the analyzes indicate that both books present specialized knowledge in the scopes "ways of presenting the content - learning potential", "associated pedagogical resource/material", with greater evidence of presence of knowledge of the scope “psychological theory associated with the learning of content” in the book Teláris Mathematica. With regard to the "most common learning errors", both books stood out for the high manifestation of specialized knowledge in contrast to low gaps.